The Relation of the Family Support with the Healthy Lifestyle of Hypertension in Family - I. G. A. Merry Mahadewi; Ni Wayan Suniyadewi; Nyoman Mudia (Stikes Wira Medika Bali, 2017)
Hypertension is a condition when the systolic blood pressure greater than 120 mmHg and diastolic blood pressure over 80 mmHg. Healthy lifestyle of hypertension as one of handling blood pressure so that family support is necessary in order to achieve compliance with management healthy lifestyle in patient with hypertension. The purpose study to determine relation of the family support with the healthy lifestyle of hypertension in family. Method: Design of study deskriptif corelasional with cross sectional design. Study was conducted at UPT Kesmas Gianyar I with forty three respondents was taken by consecutive sampling. Family support and healthy lifestyle of hypertension by questionnaire and analyzing using by rank spearman test. Result: Research of study showard most respondents have a high family support 41,9% and a most respondents has enough healthy lifestyle 58,1%. The result of analysis obtained p=0.012<α (α=0.05), which means there is a significant a relation of the family support with healthy lifestyle of hypertension in family. Discussion: Device for community to implement the healthy lifestyle of to controlled blood pressure in patient with hypertension.